دور الامتثال في حماية البنوك بالإشارة إلى البنوك العاملة بالجزائر: The role of compliance in the protection of banks by reference to banks operating in Algeria - زيدان عبد الرزاق (Journal of North African Economies, 2025)
This research aims to determine the role of compliance with banking laws and legislation in protecting banks and maintaining their stability and to avoid the risks of non-compliance that adversely affect banks' reputation from both customer and supervisory and supervisory authorities. We found from this research several findings: The adherence to laws issued by supervisory and controlling authorities helps banks to avoid fraud behaviors and illegal actions banking, such as the whitewashing of funds, the financing of terrorism and avoiding the risks of non-compliance that could ultimately lead to the collapse and bankruptcy of banks, hence damage to the banking system as a whole. The study presented several proposals; the most important was the need to activate the internal control mechanism in banks and financial institutions, in particular to monitor their compliance with banking legislation, notably to monitor their compliance with banking legislation, with regard to compliance with applicable laws and legislation in the banking activity, supervisory authorities should tighten their oversight.